2019
DOI: 10.1093/cdn/nzz064
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Identification and Consumption of Whole-Grain Foods in a Low-Income Population

Abstract: Background US Dietary Guidelines include recommendations to increase whole-grain consumption, but most Americans, especially low-income adults, fail to consume adequate amounts. Objectives The aim of this study was to determine major factors that may affect whole-grain consumption among low-income adults. Methods A mixed methods approach including a whole-grain food identification activity and in-depth interview was used to determine the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 44 publications
(50 reference statements)
7
34
0
Order By: Relevance
“…This is in tandem with a study on the consumption of WGs foods from brewers' spent grain, which indicates that hereditary consumers of whole grain foods will be more receptive to its consumption as compared to their refined foods counterpart [133]. Some studies have also indicated barriers for consuming WG foods such as the lack of knowledge about its health benefits, challenges with cooking/preparation time, negative sensory perception, perceived cost, and the lack of availability of whole grains [134][135][136].…”
Section: Future Perspectivementioning
confidence: 66%
“…This is in tandem with a study on the consumption of WGs foods from brewers' spent grain, which indicates that hereditary consumers of whole grain foods will be more receptive to its consumption as compared to their refined foods counterpart [133]. Some studies have also indicated barriers for consuming WG foods such as the lack of knowledge about its health benefits, challenges with cooking/preparation time, negative sensory perception, perceived cost, and the lack of availability of whole grains [134][135][136].…”
Section: Future Perspectivementioning
confidence: 66%
“…These population subgroups also presented an increasing trend in the amount of grain foods meeting the ≤10:1 ratio consumed, except for individuals in the lowest income category (family income per capita less than 1 minimum wage), which reinforce the importance of affordability in order to improve the consumption of healthful grain foods. Prior study among low-income adults in the USA found the ability to correctly identify wholegrain foods and the perception of higher cost as the major barriers to increase the consumption of these foods (9) . Nevertheless, the proportion of the population consuming any grain food meeting the ≤10:1 ratio increased even among lower income categories, from 4 % in 2003 to 12 % in 2015, which points to an improvement during this time.…”
Section: Discussionmentioning
confidence: 99%
“…The required increase in wholegrain foods intake is hindered by the population's inability to correctly identify these foods, along with the ongoing debate on the definition of what constitutes a wholegrain food (7)(8)(9) . In this sense, the presence per 10 g of carbohydrate of at least 1 g of fibre (≤10:1 ratio) was proposed by the American Heart Association as a metric to identify fibre-rich whole grains (10) .…”
mentioning
confidence: 99%
“…According to AACCI (American Association of Cereal Chemists International) 'wholegrains can be defined as the intact, cracked, ground or flaked caryopsis, whose anatomical parts, endosperm, bran and germ are found in the same quantity as present in the intact original grain'. Wholegrains are a rich source of nutrients and are more nutritious than refined ones as they contain higher amounts of dietary fibres, macro-and micronutrients and bioactive compounds that are retained from germ and bran fractions (Chea & Mobley, 2019). Wholegrains have a beneficial effect on several lifestylerelated diseases like cardiovascular diseases, constipation, colon cancer, type-II diabetes, weight management (Reynolds et al, 2019) and also influence the beneficial metabolism of glucose, blood lipids, adiposity and inflammation markers (Roager et al, 2019).…”
Section: Introductionmentioning
confidence: 99%